Nymphoides peltata Root Extracts Improve Atopic Dermatitis by Regulating Skin Inflammatory and Anti-Oxidative Enzymes in 2,4-Dinitrochlorobenzene (DNCB)-Induced SKH-1 Hairless Mice - Tae-Young Kim; No-June Park; Hyun Jegal; Jin-Hyub Paik; Sangho Choi; Su-Nam Kim; Min Hye Yang (MDPI AG, 2023)
Nymphoides peltata is widely used pharmacologically in Traditional Chinese Medicine and Ayurvedic medicine as a diuretic, antipyretic, or choleretic and to treat ulcers, snakebites, and edema. Previous studies have shown that phytochemicals from N. peltata have physiological activities such as anti-inflammatory, anti-tumor, and anti-wrinkle properties. Nevertheless, research on the anti-atopic dermatitis (AD) effect of N. peltata extract is limited. This study was undertaken to assess the in vitro and in vivo anti-atopic and antioxidant activities of a 95% EtOH extract of N. peltata roots (NPR). PI-induced RBL-2H3 cells and two typical hapten mice (oxazolone-induced BALB/c mice and 2,4-dinitrochlorobenzene (DNCB)-induced SKH-1 hairless mice) were used to investigate the effect of NPR extract on AD. The expressions of AD-related inflammatory cytokines, skin-related genes, and antioxidant enzymes were analyzed by ELISA, immunoblotting, and immunofluorescence, and skin hydration was measured using Aquaflux AF103 and SKIN-O-MAT instruments. The chemical composition of NPR extract was analyzed using an HPLC-PDA system. In this study, NPR extracts were shown to most efficiently inhibit IL-4 in PI-induced RBL-2H3 cells and AD-like skin symptoms in oxazolone-BALB/c mice compared to its whole and aerial extracts. NPR extract markedly reduced DNCB-induced increases in mast cells, epidermal thickness, IL-4 and IgE expressions, and atopic-like symptoms in SKH-1 hairless mice. In addition, NPR extract suppressed DNCB-induced changes in the expressions of skin-related genes and skin hydration and activated the Nrf2/HO-1 pathway. Three phenolic acids (chlorogenic acid, 3,5-dicaffeoylquinic acid, and 3,4-dicaffeoylquinic acid) were identified by HPLC-PDA in NPR extract. The study shows that NPR extract exhibits anti-atopic activities by inhibiting inflammatory and oxidative stress and improving skin barrier functions, and indicates that NPR extract has potential therapeutic use for the prevention and treatment of AD.